Agricultural Sector Investment Need in Increasing Economic Growth - Nasir, Muhammad; Faizun, Nurul; Syechalad, Mohd. Nur (Universitas Negeri Semarang, 2017)
This paper is aimed to analyze the need of investment in agricultural sector in increasing economic growth in Aceh Province. The priority in developing agricultural commodities increases economic growth in Aceh Province. This research used secondary data sources from Indonesian Statistic Board (BPS) and other related data sources. Meanwhile, the research method used is Incremental Capital Output Ratio (ICOR) Analysis. Based on the research results, it is found that the ICOR in crop plantation, livestock, forestry, and fisheries sub sectors are 2.926, 0.000, 0.108, and 0.298. This means that in achieving economic growth by 1 percent in all four commodities, its need the growth of investment in crop plantation, livestock, forestry, and fisheries sub sectors as much as 2.926, 0.000, 0.108, and 0.298 percent each. Furthermore, in achieving 4 percent economic growths, the developing of commodities that have the effect on economic welfare, it needs the investment for the five years period as much as 286 billion rupiah or equivalent with 58.1 percent of Gross Domestic Regional Product (GDRP) of Aceh Province. Thus, based on the research results, it is recommended that the Aceh Government should promote investment in agricultural sector in promoting economic growth in Aceh Province.